PERILAKU PETANI DALAM PEMBELIAN BIBIT KOPI ARABIKA (Coffea arabica) ANDUNG SARI I PETANI KOPI KABUPATEN KARO - Posman HP Marpaung; Lyndon Parulian Nainggolan; Fandri Siburian; Iyon Ginting (Universitas Quality, 2021)
Andung sari 1 coffee seeds made in Suka Mbayak Village have a large fruit production, but not too high, do not have many wild shoots, are resistant to pests and stems so that farmers are more interested in planting Arabica coffee seeds (Coffea arabica) Andung sari varieties 1. The research method in the research area was determined purposively or deliberately based on the primary data of 20 families of Andung sari 1 arabica coffee farmers, with the characteristics of the respondents described by gender, education, age and occupation. Based on the results of respondents in the field according to gender, the male andung sari coffee farmers were the most respondents (90.1%). Based on the latest education, the most respondents were junior high school and high school students (38.8%). According to respondents, the most age groups were respondents aged 31 - 40 years (65.6%) and while based on job respondents the most respondents were coffee farmers (60.5%). Based on the results of the above research, it can be concluded that cultural, social, personal and psychological factors simultaneously have a positive and significant effect on the decision to purchase Arabica coffee seedlings of Andung Sari 1 variety, this can be seen in the value of F count> F table (18,144> 2,494 ) and the significant value is smaller than the significant level 0.05 (0.000 <0.05), then the fifth hypothesis is accepted, meaning that it simultaneously has a positive influence on the decision to purchase Andung Sari 1 coffee seedlings.